Pure brookite type titanium dioxide nanorod catalyst with regulated crystal face as well as preparation method and application of pure brookite type titanium dioxide nanorod catalyst
The pure plate titanium-type titanium dioxide nanorod catalyst exposed (120), (111) and (110) active crystal surfaces was synthesized by hydrothermal method, which solved the low NOx removal efficiency and difficulty in synthesis of pure plate titanium-type TiO2 in the prior art. The problem of this has achieved efficient and low energy consumption NOx removal and improved catalyst stability.
Patent Information
- Application Number
- CN202411612222.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively remove NOx, especially to trace levels, and it is difficult to remove it to trace levels, and the energy consumption is large, and the synthesis of pure plate titanium-type TiO2 is difficult and the thermodynamics is in a metastable state, resulting in its application in the field of photocatalytics. limit.
The pure plate titanium-type titanium dioxide nanorod catalysts exposed to (120), (111) and (110) active crystal surfaces were synthesized by hydrothermal method, and the crystal surface structure was adjusted using template agents and additives to improve the selectivity and stability of the catalyst.
It achieves efficient NOx removal, has excellent nitrate ion selectivity, reduces environmental secondary pollution, has good catalyst stability, is suitable for industrial production, and significantly improves photocatalytic performance.
Smart Images

Figure CN119259017A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocatalysts and photocatalysis, and in particular to a pure brookite-type titanium dioxide nanorod catalyst with regulated crystal surface and a preparation method thereof, as well as application of the catalyst in the treatment of environmental pollutants NOx. Background Art
[0002] Environmental pollution is one of the major issues that affect human life and the ecological stability of the earth. Toxic gases such as nitrogen oxides (NOx, 95% NO), ozone (O3), sulfur dioxide (SO2), carbon monoxide (CO), carbon dioxide (CO2), methane (CH4), etc. are one of the factors that cause environmental pollution. Among them, NOx is the main cause of ozone layer depletion, photochemical smog, acid rain and respiratory diseases. According to the International Energy Agency (IEA), about 6.5 million people die from NOx air pollution every year. Therefore, over the past few decades, people have made a lot of efforts to overcome this problem, including selective catalytic oxidation, selective catalytic reduction, liquid solvent absorption and electron beam absorption. However, these technologies consume a lot of energy and cannot remove NOx below 200ppm. Therefore, it is crucial to develop a low-energy and environmentally friendly technology that can remove NOx to trace levels.
[0003] In recent years, catalysts with different activities and selectivities have been widely studied in different research fields. Recently, semiconductor photocatalysts, such as TiO2, ZnO, Bi2WO3, WO3, and g-C3N4, have attracted great attention due to their directional conversion under sunlight. Among them, TiO2 is considered to be the most promising photocatalyst for NOx removal due to its high photocatalytic activity, high chemical stability, and low cost. TiO2 is considered to be the gold standard photocatalyst for gas-phase photooxidation reactions. In addition, TiO2 has a band structure suitable for the generation of hydroxyl radicals (OH·) by oxidative adsorption of water and oxygen reduction. Anatase, rutile, and brookite are the three main crystal forms of TiO2 in nature, which are composed of edge-connected or shared dislocation TiO6 octahedra. Among these forms, brookite is the least studied form, which is due to the difficulty in synthesizing pure brookite TiO2 and its thermodynamics in a metastable state. Different synthesis methods of brookite TiO2 have been reported, such as nanorods, nanotubes, nanoflowers, nanospheres, and nanosheets. However, these methods are still insufficient in obtaining pure brookite TiO2 with high selectivity. There is still a need for a suitable method to synthesize pure brookite TiO2 with high activity and high selectivity.
[0004] In the photocatalytic process, the generation of electrons (e-) and holes (h+) depends on the difference in band gap energy levels between the light source and the photocatalyst. When the energy of light is greater than the band gap energy level of the photocatalyst, electrons (e-) and holes (h+) will be generated. The activity of the photocatalyst mainly depends on the competition between the formation of active free radicals and the electron-hole recombination rate. These generated electrons and holes react with the adsorbed O2 and H2O molecules respectively to generate active substances O2·- and OH·. These active substances will react with NOx to generate NO2 and NO3 - However, the fast recombination rate of photogenerated electrons and holes (10 picoseconds) is a major obstacle to the activity of photocatalysts and must be controlled. Crystal structure engineering is considered an effective way to overcome these limitations.
[0005] Crystal plane engineering is an effective method to optimize surface reactivity or improve electronic band structure. Lin et al. found that the photocatalytic activity of brookite TiO2 is highly dependent on the crystal plane, where the (201) crystal plane plays an oxidizing role in the photocatalytic process, while the (210) and (101) crystal planes play a reducing role (J.Am.Chem.Soc., 2012, 134, 8328-8331). Similarly, Katsumata et al. reported that the (001) and (210) crystal planes of pure brookite TiO2 are superior to standard TiO2 Degussa P25 in the photocatalytic reaction of acetaldehyde decomposition to produce CO2 (ACS Appl.Mater.Interfaces, 2012, 4, 4846-4852). Recently, Zhou et al. found that the (111) crystal plane of brookite nanosheets, the (121) crystal plane of brookite nanorods, and the (211) crystal plane of brookite nanosheets performed better in the catalytic efficiency of benzene hydrogenation to cyclohexene (Chem. Eng. J., 2024, 484, 149635-149652). Summary of the invention
[0006] The purpose of the present invention is to provide a pure brookite-type titanium dioxide nanorod catalyst with controlled crystal surface and a preparation method thereof, as well as application in the field of environmental pollution control.
[0007] In order to achieve the above technical objectives, the present invention provides the following technical solutions:
[0008] In one aspect, the present invention provides a pure brookite-type titanium dioxide nanorod catalyst with crystal face regulation, which exposes (120), (111) and (110) active crystal faces.
[0009] The present invention also provides a method for preparing the crystal plane-controlled pure brookite-type titanium dioxide nanorod catalyst, comprising the following steps:
[0010] 1) mixing a TiO2 precursor and a template agent in a solution of an additive according to a preset ratio to obtain a mixed solution;
[0011] 2) transferring the mixed solution obtained in step 1) to a hydrothermal synthesis reactor, heating for reaction, collecting the product by centrifugation after the reaction is completed, and then washing and removing impurities from the product to obtain an intermediate product;
[0012] 3) The intermediate product obtained in step 2) is dried, ground into powder, and then calcined to obtain the pure brookite-type titanium dioxide nanorod catalyst.
[0013] Furthermore, in step 1), the TiO2 precursor includes di(2-hydroxypropionic acid) diammonium dihydroxide titanium (C6H18N2O8Ti); the template includes sodium lactate; and the additive includes urea.
[0014] Furthermore, in step 1), the volume ratio of the TiO2 precursor to the template is 1:0.3-1:1, preferably 1:0.5-1:0.7, and more preferably 1:0.6.
[0015] Furthermore, in step 1), the final concentration of urea in the mixed solution is controlled to be in the range of 1-6M, preferably 3-6M, and more preferably 6M.
[0016] Furthermore, in step 2), the heating reaction temperature is 150-200° C., and the reaction time is 12-36 hours, preferably 180° C. for 24 hours.
[0017] Furthermore, in step 3), the calcination temperature is 400-600° C., and the calcination time is 2-5 hours, preferably calcined at 500° C. for 3 hours at a heating rate of 5° C. / min.
[0018] The present invention also provides an application of the crystal plane-regulated pure brookite-type titanium dioxide nanorod catalyst in the field of environmental pollution control.
[0019] The present invention successfully synthesized a pure brookite-type titanium dioxide nanorod catalyst with exposed (120), (111) and (110) active crystal faces by adding a template and an additive using a hydrothermal method. The approximate homogeneity of the (120), (111) and (110) crystal faces helps it to obtain the maximum NO3 - Ion selectivity. At the same time, pure brookite titanium dioxide nanorods have a high water content adsorbed on the crystal surface, which helps to improve the photocatalytic performance. In addition, pure brookite titanium dioxide nanorods introduce a large number of crystal defects, which helps to increase the amount of light absorption and enhance the photocatalytic activity and selectivity for NO3- ions.
[0020] Beneficial effects of the present invention:
[0021] The pure brookite-type titanium dioxide nanorod catalyst with controlled crystal surface prepared by the present invention has the following advantages:
[0022] (1) The preparation process is simple and easy to industrialize;
[0023] (2) High photocatalytic efficiency and good NOx removal effect;
[0024] (3) It has excellent nitrate ion selectivity, reducing secondary pollution to the environment;
[0025] (4) The catalyst has good stability and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 TEM (a and b) and HRTEM of TALH-6U-SL and its rod size distribution histogram (a), and FFT analysis of crystal planes (120), (111) and (121) of TALH-6U-SL (c).
[0027] Figure 2 1 is the XRD diagram of the pure brookite-type titanium dioxide nanorod catalyst prepared in Examples 1 to 3 and Comparative Examples 1 to 3.
[0028] Figure 3 This is a time curve of photocatalytic oxidation of NO by the photocatalyst.
[0029] Figure 4 Figure 2 shows the photon efficiency of photocatalyst for photocatalytic oxidation of NO (a) and the corresponding nitrate selectivity (b).
[0030] Figure 5 TGA diagrams of TALH-6U and TALH-6U-SL.
[0031] Figure 6 FTIR spectra of TALH-6U and TALH-6U-SL.
[0032] Figure 7 XPS spectra of TALH-6U and TALH-6U-SL (Ti 2p (a) and O1s (b)). DETAILED DESCRIPTION
[0033] The technical solution of the present invention is now further described in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the following implementation scenarios.
[0034] Experimental materials: Titanium di(2-hydroxypropionic acid) diammonium dihydroxide (TALH, C6H 18N2O8Ti, 50% w / w aqueous solution), sodium lactate (C3H5NaO3, 60% w / w aqueous solution) and urea (NH4CNO, 99%), anhydrous ethanol (C2H5OH, 99.7%). Deionized water was produced by RO / EDI equipment with a resistivity of about 18.25 MΩ.cm at 25°C.
[0035] Example 1 Synthesis of crystal surface-regulated pure brookite-type titanium dioxide nanorod catalyst 1 (labeled as TALH-6U-SL)
[0036] 5 mL TALH (C6H 18 N2O8Ti) and 3mL sodium lactate (C3H5NaO3) were mixed in a urea aqueous solution, and then deionized water was added to a total volume of 50mL. The final total concentration of urea was 6M. After complete mixing, the final solution was transferred to a 100mL polytetrafluoroethylene-lined hydrothermal reactor. The reactor was sealed, placed in an oven, and reacted at 180°C for 24 hours. Thereafter, the product was collected by centrifugation, washed three times with ethanol and deionized water to remove impurities, and dried in an oven at 70°C for 12 hours. The dried product was ground into powder with an agate mortar and calcined at 500°C for 3h at a heating rate of 5°C / min to obtain TALH-6U-SL.
[0037] Example 2 Synthesis of crystal surface-controlled pure brookite-type titanium dioxide nanorod catalyst 2 (labeled as TALH-3U-SL)
[0038] The preparation process of TALH-3U-SL is basically the same as that of Example 1, except that the final total concentration of urea is 3M.
[0039] Example 3 Synthesis of crystal surface-regulated pure brookite-type titanium dioxide nanorod catalyst 3 (labeled as TALH-1U-SL)
[0040] The preparation process of TALH-1U-SL is basically the same as that of Example 1, except that the final total concentration of urea is 1M.
[0041] Comparative Example 1 Synthesis of TALH-6U
[0042] Compared with Example 1, the difference of this comparative example is that sodium lactate is not added during the preparation process. The specific process is:
[0043] 5 mL TALH (C6H 18N2O8Ti) was mixed in a urea aqueous solution and then added to a total volume of 50 mL by adding deionized water. The final total concentration of urea was 6 M. After complete mixing, the final solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal synthesis reactor. The reactor was sealed, placed in an oven, and reacted at 180°C for 24 hours. Thereafter, the product was collected by centrifugation, washed three times with ethanol and deionized water to remove impurities, and dried in an oven at 70°C overnight. The dried product was ground into powder with an agate mortar and calcined at 500°C for 3h at a heating rate of 5°C / min to obtain the TALH-6U.
[0044] Comparative Example 2 Synthesis of TALH-3U
[0045] Compared with Comparative Example 1, the only difference in this comparative example is that the final total concentration of urea is 3M.
[0046] Comparative Example 3 Synthesis of TALH-1U
[0047] Compared with Comparative Example 1, the only difference in this comparative example is that the final total concentration of urea is 1M.
[0048] In order to further understand the properties of the pure brookite-type titanium dioxide nanorod catalyst obtained by the above method with controlled crystal surface, the following experiment is taken as an example for analysis:
[0049] Test Example 1: Transmission Electron Microscopy (TEM, Jeol)
[0050] The structural morphology of the TALH-6U-SL catalyst prepared in Example 1 was observed by TEM and HRTEM experiments. Figure 1 As shown. Figure 1 As can be seen in a and b, TALH-6U-SL has a distinct rod-like morphology with an average size of about 125 nm. The high-resolution transmission electron microscopy image (c) of TALH-6U-SL nanorods shows that the measured visible lattice spacing of 0.23 nm and 0.22 nm belongs to the (111) and (121) lattice spacings of the TALH-6U-SL atomic planes. In addition, the high-resolution transmission electron microscopy image of TALH-6U-SL shows that (111) and (121) are the more exposed crystal planes of TALH-6U-SL nanorods.
[0051] Test Example 2: XRD powder diffraction
[0052] The TALH-6U-SL, TALH-3U-SL, TALH-1U-SL, TALH-6U, TALH-3U, and TALH-1U samples prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to powder XRD analysis on a Rigaku diffractometer using 0.154 nm Cu Kα radiation.
[0053] The X-ray diffraction spectrum results are as follows Figure 2 The results show three typical diffraction peaks of pure brookite-type titanium dioxide nanorod catalyst at 2θ of 25.13, 25.46 and 30.26. Figure 2 The peak characteristics shown in a show that the peak positions of TALH-6U-SL, TALH-3U-SL, TALH-1U-SL, TALH-6U, TALH-3U, and TALH-1U are at the same 2θ value, and no peak shift occurs after adding sodium lactate. Figure 2 The difference in peak intensity can be clearly seen in b. The peak intensities of (121) and (111) increase with increasing urea concentration (TALH-1U-SL to TALH-6U-SL). In the case of TALH-6U, the peak intensities of (121) and (111) are approximately 1:1. In the case of TALH-6U-SL, the peak intensity of (111) is higher than that of (121), indicating that sodium lactate and urea play an important role in regulating the crystal face structure.
[0054] The specific surface area, pore size, pore volume and average crystal domain of (120), (111) and (121) XRD peaks of TALH-1U, TALH-1U-SL and TALH-6M-SL were obtained by Scherrer analysis, and the results are shown in Table 1. It can be seen from the results that the surface area, pore size and pore volume increased slightly compared with TALH-1U by adding sodium lactate (TALH-1U-SL). Among them, the size of the (120) crystal plane of TALH-1U-SL increased by 1.3 times. By increasing the urea concentration from 1M to 6M and then adding sodium lactate (TALH-6U-SL), the surface area, pore size and pore volume decreased slightly, but the size of the two main crystal planes (111) and (121) was about 1:1, which was slightly higher than the (120) crystal plane of TALH-6U-SL. This means that all crystal planes can be used for photocatalytic activity testing, and the high availability and high stability of the (111) and (121) crystal planes are beneficial to the enhancement of the photocatalytic activity of TALH-6U-SL.
[0055] Table 1 Specific surface area, pore size, pore volume and average crystal domain results of (120), (111) and (121) XRD peaks of TALH-1U, TALH-1U-SL and TALH-6U-SL
[0056] sample <![CDATA[SSA(m 2 / g)]]> Pore size (nm) <![CDATA[Pore volume (cm 3 / g)]]> <![CDATA[d 120 (nm)]]> <![CDATA[d 111 (nm)]]> <![CDATA[d 121 (nm)]]> TALH-1U 42.56 15.24 0.165 19.94 33.43 28.87 TALH-1U-SL 43.11 16.15 0.178 25.63 31.04 28.11 TALH-6U-SL 39.88 16.07 0.159 20.86 21.49 21.89
[0057] Test Example 3: Photocatalytic NOx removal test
[0058] First, 100 mg of the catalysts prepared in Examples 1-3 and Comparative Examples 1-3 were dissolved in 0.5 mL of deionized water and then dropped onto a 24 cm2 The mixture was placed on a glass plate. Dry at 50 °C for 3 h and exposed to 365 nm UVA light for 12 h to remove impurities. The NO concentration at the inlet was adjusted to 1000 ± 50 ppb, 30 L min -1 The flow rate was 200 μm and the humidity was 50%. A Thorlab LED 365 nm light source was used as the light source and the light intensity was adjusted to 1.0 mW / cm 2 The concentrations of NO and NO2 were estimated by a NOx analyzer. Photon efficiency (ξ) and NOx removal selectivity were calculated using equations 1 and 2.
[0059]
[0060]
[0061] The photocatalytic NOx removal test was carried out according to ISO standard method (22197-1), where t0 and t1 are the UV irradiation time intervals, A represents the gas coefficient constant (2.045×10 -12 mol s1), X represents the NO oxidation or NO2 generation rate in ppb, and I represents the incident photon flux ( E i nste i n s-1).
[0062] Figure 3 , Figure 4 The results show that the catalysts prepared in Examples 1-3 and Comparative Examples 1-3 all have photocatalytic activity, and TALH-6U-SL has approximately the same (120), (111) and (110) crystal faces, and its performance is better than other catalysts, including the standard TiO2-P25 catalyst. Importantly, compared with most catalysts that can only convert nitrogen oxides into nitrogen dioxide, the photon efficiency (ξ) ( Figure 4 a) The results show that TALH-3U-SL and TALH-6U-SL catalysts can convert nitrogen oxides into environmentally friendly nitrate ions (NO3 - ), which is a key parameter in NOx reduction applications. Figure 4As shown in Figure b, when sodium lactate is added and more (111) crystal faces are formed, the prepared crystal face-regulated pure brookite-type titanium dioxide nanorod catalysts oxidize NOx to nitrate ions with selectivity of 21.8% (TALH-1U-SL), 53.0% (TALH-3U-SL) and 68.8% (TALH-6U-SL), which are significantly higher than 9.9% (TALH-1U), 11.8% (TALH-3U) and 10.5% (TALH-6U) of the pure brookite-type titanium dioxide nanorod catalysts synthesized without adding sodium lactate. In addition, the selectivity of the pure brookite-type titanium dioxide nanorod catalyst synthesized with approximately equal amounts of (120), (111) and (110) crystal faces is much higher than that of the standard TiO2-P25 (14%). Importantly, the best catalyst, TALH-6U-SL, showed approximately 6.8 and 4.9 times higher selectivity than TALH-6U and the standard TiO2-P25 catalyst, respectively.
[0063] Test Example 4: Thermogravimetric Analysis and FTIR Characterization
[0064] The high selectivity of TALH-6U-SL is due to the more uniform availability of stable and active (111) and (121) crystal facets. Large adsorption capacity favors adsorption on specific crystal facets. The crystallinity of the nanomaterials is strongly correlated with the number of physically adsorbed H2O and O2 defects in the TiO2 lattice, as low crystallinity leads to the formation of defects on the TiO2 surface. During the photocatalytic process, photogenerated electrons (e-) and holes (h+) are generated on the conduction band and valence band states. These photogenerated electrons (e-) and holes (h+) react with adsorbed molecular oxygen (O2ads) and water (H2Oads) to generate superoxide anion radicals (O2·-) and hydroxyl radicals (OH·). These radicals further react with adsorbed nitric oxide (NOads) on the photocatalyst surface to form nitrate ions (NO3-). Trapped holes and surface defects (i.e., vacancies) play an important role in nitrate ion selectivity during photocatalytic NOx reduction.
[0065] To analyze the effect of adsorbed water molecules, the amount of water was calculated using thermogravimetric analysis (TGA). Figure 5 The TGA results in Figure 2 show that the weight loss percentage in TALH-6U-SL is -3.86%, while that in TALH-6U is about -1.69%. The amount of weight loss refers to the water molecules adsorbed on the surface of the synthesized photocatalyst. The amount of water adsorbed on TALH-6U-SL is much higher than that on TALH-6U, which is beneficial for improving NO3 - The selectivity of ions plays an important role. To verify this result, both TALH-6U-SL and TALH-6U photocatalysts were further characterized by infrared spectroscopy (FTIR) using the KBr film method. Figure 6 The stretching and bonding vibration peaks of water are around 3440 cm -1 and 1625cm -1 The results show that TALH-6U-SL has more adsorbed crystal water molecules than TALH-6U.
[0066] Test Example 5: XPS Analysis
[0067] To characterize the defects, XPS analysis was performed. Figure 7 High-resolution spectra of TALH-6U and TALH-6U-SL photocatalysts are shown. Figure 7 In a, the two peaks of TALH-6U sample at 458.9 and 464.8 eV belong to Ti 4+ The binding energy indicates that the binding of Ti to oxygen is the same as that of pure brookite-type titanium dioxide. Importantly, the two peaks of TALH-6U-SL are -0.3 and -0.5 eV lower than those of TALH-6U, respectively, which means that there are oxygen vacancies in the lattice. These oxygen vacancies contribute to the improvement of the activity and selectivity of the photocatalyst. The difference in O 1s peak ( Figure 7 b) further demonstrates the presence of oxygen vacancies. For TALH-6U, the O1s peak at 530.2 eV indicates the presence of oxygen in the TiO2 lattice. In contrast, the O1s peak of TALH-6U-SL shifted from 530.2 to 529.6 eV, further indicating the formation of oxygen defects in the TiO2 lattice. Another signal appearing at 531.4 eV corresponds to the hydroxyl group at the oxygen vacancy in the TALH-6U catalyst. In TALH-6U-SL, the binding energy decreases from 531.4 eV to 530.9 eV, indicating that oxygen species are easily adsorbed, which is conducive to the activation of oxygen.
Claims
1. A pure brookite-type titanium dioxide nanorod catalyst with controlled crystal surface, characterized in that: The pure brookite-type titanium dioxide nanorod catalyst exposes (120), (111) and (110) active crystal faces.
2. A method for preparing the pure brookite-type titanium dioxide nanorod catalyst with crystal plane control as claimed in claim 1, comprising the following steps: 1) mixing a TiO2 precursor and a template agent in a solution of an additive according to a preset ratio to obtain a mixed solution; 2) transferring the mixed solution obtained in step 1) to a hydrothermal synthesis reactor, heating for reaction, collecting the product by centrifugation after the reaction is completed, and then washing and removing impurities from the product to obtain an intermediate product; 3) The intermediate product obtained in step 2) is dried, ground into powder, and then calcined to obtain the pure brookite-type titanium dioxide nanorod catalyst.
3. The preparation method according to claim 2, characterized in that: In step 1), the TiO2 precursor includes di(2-hydroxypropionic acid) diammonium titanium dihydroxide; the template includes sodium lactate; and the additive includes urea.
4. The preparation method according to claim 2, characterized in that: In step 1), the volume ratio of the TiO2 precursor to the template is 1:0.3-1:
1.
5. The preparation method according to claim 2, characterized in that: In step 1), the final concentration of urea in the mixed solution is controlled to be in the range of 1-6M.
6. The preparation method according to claim 2, characterized in that: In step 2), the heating reaction temperature is 150-200° C. and the reaction time is 12-36 hours.
7. The preparation method according to claim 2, characterized in that: In step 3), the calcination temperature is 400-600° C. and the calcination time is 2-5 hours.
8. Use of the pure brookite-type titanium dioxide nanorod catalyst with controlled crystal face as claimed in claim 1 or the pure brookite-type titanium dioxide nanorod catalyst with controlled crystal face obtained by the preparation method according to any one of claims 2 to 7 in the field of environmental pollution control.